2003
DOI: 10.2337/diacare.26.3.855
|View full text |Cite
|
Sign up to set email alerts
|

Development of Congestive Heart Failure in Type 2 Diabetic Patients With Microalbuminuria or Proteinuria

Abstract: FOR THE DIABHYCAR STUDY GROUPOBJECTIVE -The DIABHYCAR (type 2 DIABetes, Hypertension, CArdiovascular Events and Ramipril) study allowed investigators to analyze factors leading to the development of congestive heart failure (CHF) in type 2 diabetic patients with abnormal urinary albumin concentration.RESEARCH DESIGN AND METHODS -Type 2 diabetic subjects of both sexes aged Ն50 years who had a urinary albumin concentration Ն20 mg/l were randomly allocated to 1.25 mg/day ramipril or placebo in addition to their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
1
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 42 publications
4
84
1
12
Order By: Relevance
“…282 On the other hand, T2DM increased the risk of hospitalization in patients with heart failure in the BEta blocker STroke trial (BEST) 283 (RR1.16; P = 0.027). In the Metoprolol CR/XL Randomised Intervention Trial in Congestive Heart Failure (MERIT-HF), 284 patients with heart failure and T2DM had 1-year hospitalization of 31%, compared with 24% forthose free from DM.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…282 On the other hand, T2DM increased the risk of hospitalization in patients with heart failure in the BEta blocker STroke trial (BEST) 283 (RR1.16; P = 0.027). In the Metoprolol CR/XL Randomised Intervention Trial in Congestive Heart Failure (MERIT-HF), 284 patients with heart failure and T2DM had 1-year hospitalization of 31%, compared with 24% forthose free from DM.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…In the DIABHYCAR study, the combination of heart failure and T2DM resulted in a mortality rate 12-times-as great as in patients with T2DM but without heart failure (36 vs.3%). 282 BEST and Studies Of Left Ventricular Dysfunction (SOLVD) 283,285 reported T2DM as an independent predictor of mortality, mostly in ischaemic heart failure.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…In several studies, the incidence of heart failure was two-and fourfold higher in patients with diabetes mellitus than in those without (54)(55)(56)(57)(58)(59). The development of heart failure in diabetes mellitus significantly increases mortality (61). Up to 30% of heart failure patients have diabetes mellitus (55,60,62).…”
Section: Cardiomyopathy With Diabetes Mellitus or Obesitymentioning
confidence: 99%
“…How should I treat it? Although an increase in glycosylated hemoglobin in patients with diabetes mellitus is a risk factor for developing heart failure (54,61,70,71), studies have not demonstrated that glycemic control significantly reduces the incidence of heart failure (72). However, the 2003 Canadian Diabetes Association clinical practice guidelines for the prevention and management of diabetes in Canada (73) recommend that most patients with type 1 or 2 diabetes should be targeted to achieve a glycosylated hemoglobin level of 7.0% or less.…”
Section: Cardiomyopathy With Diabetes Mellitus or Obesitymentioning
confidence: 99%
“…Data from the National Health Examination Survey I (22) and the Framingham study (17) have shown the incidence of heart failure in patients with diabetes mellitus to be two-and fourfold higher, respectively, than in patients without diabetes mellitus. While an increase in glycosylated hemoglobin (HbA1C) among patients with diabetes mellitus is a recognized risk factor for heart failure (23)(24)(25)(26)(27), no study to date has demonstrated that improved glycemic control significantly reduces the incidence of heart failure (28 …”
Section: Diabetes Mellitusmentioning
confidence: 99%